Menggali Gaya Kepemimpinan Demokratis: Studi Deskriptif Pada Pemimpin Kristen dalam Pelayanan - Zebua, Eka Kurniawan; Angelina, Claudia (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
This study explores the application of democratic leadership in church ministry, emphasizing congregation participation, team collaboration, and Biblical values such as humility and service. The research background highlights the need for effective leadership to build harmonious relationships between leaders and congregations. A qualitative literature study was conducted to examine key elements of democratic leadership in Christian ministry contexts. The findings reveal that democratic leadership enhances congregation involvement in decision-making, strengthens effective communication, and fosters harmonious teamwork within church ministries. This leadership style reflects the principles of Jesus Christ’s servant leadership, centered on service and love. In conclusion, democratic leadership positively impacts the quality of church ministry, creating an inclusive environment and achieving collective goals effectively.